Evaluación "in vitro" de compuestos volátiles de ajo sobre el crecimiento de Xanthomonas axonopodis pv. citri - Mitidieri, Mariel Silvina; Brambilla, Maria Virginia; Piris, Estela Beatriz; Peralta, Romina; Sanchez, Florencia (EEA Concordia, INTA, 2023)
Poster